Impact of Surfactant Addition on Oxygen Mass Transfer in a Bubble Column. Issue 1 (3rd December 2014) - McClure, Dale D.; Lee, Ai Chia; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Abstract The impact of sparger design and surfactant addition on the oxygen transfer rate in a bubble column was examined. Additionally, measurements were also made of the holdup and bubble size distribution, allowing both the interfacial area for mass transfer and the liquid film mass transfer coefficient to be determined for a range of industrially relevant superficial velocities. It was found that for the velocity range examined changes in the superficial velocity had a minimal impact on the observed value of liquid film mass transfer coefficient. In contrast, addition of both hydrophilic and hydrophobic surface‐active compounds led to an approximately threefold reduction in liquid film mass transfer coefficient.